2014
DOI: 10.1037/xap0000020
|View full text |Cite
|
Sign up to set email alerts
|

Sharing a driver’s context with a caller via continuous audio cues to increase awareness about driver state.

Abstract: In an experiment using a driving simulator we investigated whether sharing information of a driver's context with a remote caller via continuous audio cues can make callers more aware of the driving situation. Increased awareness could potentially help in making the conversation less distracting. Prior research has shown that although sharing context using video can create such beneficial effects, it also has some practical disadvantages. It is an open question whether other modalities might also provide suffi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0

Year Published

2015
2015
2017
2017

Publication Types

Select...
3
2

Relationship

3
2

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 54 publications
1
11
0
Order By: Relevance
“…Our results confirm the classical result in driver distraction research (e.g., [1,9,10,28,29,33,45,46,51]) that secondary tasks distract from looking at the road (RQ1, Figure 4) and result in longer response times to incidents (RQ3, Figure 7). Our results also suggest that pre-alerts can mitigate some of these problems.…”
Section: Implications For Theorysupporting
confidence: 79%
See 2 more Smart Citations
“…Our results confirm the classical result in driver distraction research (e.g., [1,9,10,28,29,33,45,46,51]) that secondary tasks distract from looking at the road (RQ1, Figure 4) and result in longer response times to incidents (RQ3, Figure 7). Our results also suggest that pre-alerts can mitigate some of these problems.…”
Section: Implications For Theorysupporting
confidence: 79%
“…[29,44]), as in our increasing pulse pre-alert. However, there is still a wide design space to explore regarding exact choices.…”
Section: Convey Urgencymentioning
confidence: 99%
See 1 more Smart Citation
“…It has been shown that auditory icons are an effective solution when designing sounds in order to convey perceived meaning and control a driver's actions [20]. In the context of making a phone call, Janssen et al [15] used auditory icons such as real driving sounds and heart beats as direct and indirect cues to convey a drivers busyness to a caller. Their study showed the provision of auditory cues to be more effective than when no audio cues were presented.…”
Section: In-vehicle Auditory Feedbackmentioning
confidence: 99%
“…These range from preventing switching (e.g., Mark et al, 2012), to providing information about the context in which an interruption or distraction takes place (e.g., Grandhi, Schuler, & Jones, 2011;Janssen, Iqbal, & Ju, 2014), to providing training so that people better manage interruptions (e.g., Relihan, O'Brien, O'Hara, & Silke, 2010), to designing systems to mediate the interaction between users and other tasks demanding their attention (e.g., Arroyo & Selker, 2011;Iqbal & Bailey, 2010). Of course, despite the potential for the use of theory in practical settings, the link between theory and practice might not always be immediately obvious.…”
Section: Costs and Benefits Of Multitasking And Interruptionsmentioning
confidence: 99%